2009
DOI: 10.1158/1535-7163.mct-09-0256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of current methods used to analyze the expression profiles of ATP-binding cassette transporters yields an improved drug-discovery database

Abstract: The development of multidrug resistance (MDR) to chemotherapy remains a major challenge in the treatment of cancer. Resistance exists against every effective anticancer drug and can develop by multiple mechanisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…14 We thus focused on nonPgp resistance mechanisms, evaluating HuT78 CTCL sublines independently selected in romidepsin in the presence of verapamil or valspodar to prevent the emergence of Pgp-mediated resistance. 17 We probed potential resistance mechanisms in the romidepsin-resistant lines by using a high-throughput TaqMan-based quantitative RT-PCR assay, 31 finding increased INSR expression as well as increased IR protein and phospho-MEK expression. The MAPK pathway activation evidently led to suppression of the proapoptotic protein Bim, a mechanism of resistance not previously described in romidepsinselected cells.…”
Section: Discussionmentioning
confidence: 99%
“…14 We thus focused on nonPgp resistance mechanisms, evaluating HuT78 CTCL sublines independently selected in romidepsin in the presence of verapamil or valspodar to prevent the emergence of Pgp-mediated resistance. 17 We probed potential resistance mechanisms in the romidepsin-resistant lines by using a high-throughput TaqMan-based quantitative RT-PCR assay, 31 finding increased INSR expression as well as increased IR protein and phospho-MEK expression. The MAPK pathway activation evidently led to suppression of the proapoptotic protein Bim, a mechanism of resistance not previously described in romidepsinselected cells.…”
Section: Discussionmentioning
confidence: 99%
“…TLDA cards were analyzed with RQ Manager Software, and the median was normalized as described (23). We then multiplied the gene expression values by −1 for ease of interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that Taqman Low Density Arrays (TLDAs) provide the most sensitivity and specificity in measuring the expression patterns of ABC transporter genes (22,23). Therefore, we chose to configure such a platform to study multidrug resistance mechanisms in clinical cancer specimens.…”
mentioning
confidence: 99%
“…However, the sensitivity of these methods varies as the extensive comparison by Gillet and colleagues 145 showed. [11,12] While microarrays proved to be less adequate to discriminate between products of highly homologous genes, the Human ABC Transporter TaqMan Low-Density Array (TLDA) has been documented to be most sensitive and best suited for accurately quantitating individual ABC 150 transporter genes in a high-throughput format. [11,12] Therefore, when assessing the transporter profile of hPSCs and early derivatives, currently the TLDA should be the method of choice.…”
mentioning
confidence: 99%
“…[11,12] While microarrays proved to be less adequate to discriminate between products of highly homologous genes, the Human ABC Transporter TaqMan Low-Density Array (TLDA) has been documented to be most sensitive and best suited for accurately quantitating individual ABC 150 transporter genes in a high-throughput format. [11,12] Therefore, when assessing the transporter profile of hPSCs and early derivatives, currently the TLDA should be the method of choice. [13] ABC transporter mRNA levels significantly change over 155 the course of hPSC differentiation [13,14]; therefore, parallel to the examination of transporter profiles, a pluripotency array analysis should also be performed to validate the pluripotent state of the hPSCs.…”
mentioning
confidence: 99%